Early TIPS with covered stents versus standard treatment for acute variceal bleeding in patients with advanced cirrhosis: a randomised controlled trial. (August 2019) - Lv, Yong; Yang, Zhiping; Liu, Lei; Li, Kai; He, Chuangye; Wang, Zhengyu; Bai, Wei; Guo, Wengang; Yu, Tianlei; Yuan, Xulong; Zhang, Hongbo; Xie, Huahong; et al.
Summary: Background: The survival benefit of early placement of transjugular intrahepatic portosystemic shunts (TIPS) in patients with cirrhosis and acute variceal bleeding is controversial. We aimed to assess whether early TIPS improves survival in patients with advanced cirrhosis and acute variceal bleeding. Methods: We did an investigator-initiated, open-label, randomised controlled trial at an academic hospital in China. Consecutive patients with advanced cirrhosis (Child-Pugh class B or C) and acute variceal bleeding who had been treated with vasoactive drugs plus endoscopic therapy were randomly assigned (2:1) to receive either early TIPS (done within 72 h after initial endoscopy [early TIPS group]) or standard treatment (vasoactive drugs continued to day 5, followed by propranolol plus endoscopic band ligation for the prevention of rebleeding, with TIPS as rescue therapy when needed [control group]). Randomisation was done by web-based randomisation system using a Pocock and Simon's minimisation method with Child-Pugh class (B vs C) and presence or absence of active bleeding as adjustment factors. The primary outcome was transplantation-free survival, analysed in the intention-to-treat population, excluding individuals subsequently found to be ineligible for enrolment. This study is registered withClinicalTrials.gov, numberNCT01370161, and is completed. Findings: From June 26, 2011, to Sept 30, 2017, 373 patients were screened and 132 patients were randomly assigned to the early TIPS group (n=86) or to the control group (n=46). After exclusion of three individuals subsequently found to be ineligible for enrolment (two patients in the early TIPS group with non-cirrhotic portal hypertension or hepatocellular carcinoma, and one patient in the control group due to non-cirrhotic portal hypertension), 84 patients in the early TIPS group and 45 patients in the control group were included in the intention-to-treat population. 15 (18%) patients in the early TIPS group and 15 (33%) in the control group died; two (2%) patients in the early TIPS group and one (2%) in the control group underwent liver transplantation. Transplantation-free survival was higher in the early TIPS group than in the control group (hazard ratio 0·50, 95% CI 0·25–0·98; p=0·04). Transplantation-free survival at 6 weeks was 99% (95% CI 97–100) in the early TIPS group compared with 84% (75–96; absolute risk difference 15% [95% CI 5–48]; p=0·02) and at 1 year was 86% (79–94) in the early TIPS group versus 73% (62–88) in the control group (absolute risk difference 13% [95% CI 2–28]; p=0·046). There were no significant differences between the two groups in the incidence of hepatic hydrothorax (two [2%] of 84 patients in the early TIPS group vs one [2%] of 45 in the control group; p=0·96), spontaneous bacterial peritonitis (one [1%] vs three [7%]; p=0·12), hepatic encephalopathy (29 [35%] vs 16 [36%]; p=1·00), hepatorenal syndrome (four [5%] vs six [13%]; p=0·10), and hepatocellular carcinoma (four [5%] vs one [2%]; p=0·68). There was no significant difference in the number of patients who experienced other serious adverse events (ten [12%] vs 11 [24%]; p=0·07) or non-serious adverse events (21 [25%] vs 19 [42%]; p=0·05) between groups. Interpretation: Early TIPS with covered stents improved transplantation-free survival in selected patients with advanced cirrhosis and acute variceal bleeding and should therefore be preferred to the current standard of care. Funding: National Natural Science Foundation of China, National Key Technology R&D Program, Optimized Overall Project of Shaanxi Province, Boost Program of Xijing Hospital.